Efektivitas Pembelajaran Penjas Ditengah Pandemic Covid-19 - Supriyatni, Deswita; Hasmarita, Sony (STKIP Pasundan, 2022)
This study aims to reveal field data by explaining what was revealed in the field, analyzing and concluding research results. This research uses descriptive research with the process of collecting and compiling data, as well as analyzing and interpreting the data. The population in this study were students in class 5 A with a total of 28 people and 5B 2 at SD Negeri 260 Griya Bumi Antapani Bandung City with a total of 53 students. In this study the sampling technique that the author used was purposive sampling, the sample used was 260 Griya Bumi Antapani Public Elementary School, Bandung City. After collecting the questionnaires, it can be seen that the Effectiveness of Physical Education Learning in the Midst of the Covid-19 Pandemic as many as 50% of students felt a change in effectiveness in Physical